Swimmy - Lionni, Leo, 1910-1999. ([New York : Random House, 1963)
A little black fish in a school of red fish figures out a way of protecting them all from their natural enemies.
"Knopf/Pantheon pinwheel books."
G4
Keywords: Fishes -- Fiction